2017
DOI: 10.3201/eid2309.161594
|View full text |Cite
|
Sign up to set email alerts
|

Use of Blood Donor Screening to Monitor Prevalence of HIV and Hepatitis B and C Viruses, South Africa

Abstract: Among 397,640 first-time blood donors screened in South Africa during 2012–2015, HIV prevalence was 1.13%, hepatitis B virus prevalence 0.66%, and hepatitis C virus prevalence 0.03%. Findings of note were a high HIV prevalence in Mpumalanga Province and the near absence of hepatitis C virus nationwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 12 publications
2
19
2
Order By: Relevance
“…Despite the 2.6% HIV sero-positivity in our study which is lower than from several sub-Saharan Africa countries, where HIV prevalence ranges from 3 to 5% [44], it is much higher than 0.1% Jijiga Ethiopian Somali region [19], a 1.6% magnitude from both Yrgalem and Hawassa studies, South Ethiopia [20, 45] 0.18, 1 and 1.13% reports from Eritrea, Nyala Hospital western Sudan and South Africa respectively [34, 35, 46], 0.4% in Khartoum [47], and from Egypt in which it was no cases reported [48]. The higher report from our study is probably due to the rise in seropositivity of HIV among the general population recently, the highest geographic distributions of HIV infection in the study area which is similar to Ethiopian national data [49].…”
Section: Discussionmentioning
confidence: 48%
“…Despite the 2.6% HIV sero-positivity in our study which is lower than from several sub-Saharan Africa countries, where HIV prevalence ranges from 3 to 5% [44], it is much higher than 0.1% Jijiga Ethiopian Somali region [19], a 1.6% magnitude from both Yrgalem and Hawassa studies, South Ethiopia [20, 45] 0.18, 1 and 1.13% reports from Eritrea, Nyala Hospital western Sudan and South Africa respectively [34, 35, 46], 0.4% in Khartoum [47], and from Egypt in which it was no cases reported [48]. The higher report from our study is probably due to the rise in seropositivity of HIV among the general population recently, the highest geographic distributions of HIV infection in the study area which is similar to Ethiopian national data [49].…”
Section: Discussionmentioning
confidence: 48%
“…This decrease is expected and results from many factors including the implementation by the NBTS of stringent interventions recommended by WHO to exclude high risk potential blood donors and HBV/HIV treatment programs. Similar trends have been observed in neighboring countries [25,26]. However, these data may not be applicable to the general population as they excluded persons vaccinated at birth who were less than 16 years during the time of study and high-risk populations who could not donate blood [27].…”
Section: Discussionmentioning
confidence: 59%
“…In SSA, the median risk of being infected with HBV from a blood transfusion has been estimated at 4.3 infections per 1,000 units, and 28,595 HBV infections per year are estimated to occur [5][6][7]. The transmission risk of HBV remains even after HBV NAT has been performed on each donated blood unit [8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, despite a historically safe blood/ blood products supply system, haemophiliacs and those who received blood/blood products before 1992 were at risk, with 17% of our cohort sharing this as a risk factor. [16][17][18][19] Additionally, we have demonstrated that unsafe medical practices are a risk factor (10%). In a significant proportion of patients (26%) no clear mode of acquisition was identified.…”
Section: Discussionmentioning
confidence: 99%